IMPACT OF THE AUDIT COMMITTEE AND AUDIT QUALITY ON BANKING EARNINGS QUALITY - Sriwati , Sriwati; Verawati , Verawati; Kurniawati, Herni (International Journal of Application on Economics and Business, 2024)
The purpose of the research is to prove empirically how the characteristics of the Audit Committee, namely the characteristics of independence, size / number, and financial expertise (accounting), can improve the quality of earnings generated by banks listed on the Indonesia Stock Exchange. The research method used is quantitative description using annual report data. The research sample is Banking companies in the period 2019-2022. The results of this study prove that the independence and number of audit committees can improve the quality of banking profits, while the expertise and accounting expertise of the audit committee cannot improve or reduce the quality of Indonesian banking earnngs.